1990
DOI: 10.1111/j.1468-2435.1990.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Migrants' Remittances on the Egyptian Economy

Abstract: "The main objective of this paper is to evaluate the impact of the large remittances made by Egyptian migrants to their home country on the Egyptian economy. In order to study this impact, we use the implications of the standard Keynesian model. We estimated the structural equations of the model using annual data for the Egyptian economy over the period from 1970 to 1984.... The results suggest that remittances have had a strong positive impact on GNP in Egypt." The authors note that remittances especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Research on international migration in Pakistan has primarily addressed a number of concerns which can be summarized as (i) to establish the magnitude and demographic profiles of the out-migrants (ii) the returnmigrant (iii) implications of manpower experts at the macro-level and its broad aggregates (employment of labor force, GNP growth, savings, private investment) and consumption, and (iv) balance of payments [20]. Specifically, the utilization of remittances by migrants' households and by migrant on his return has been the subject of much empirical research mainly to search for incentives and policy prescriptions to channel these resources into productive uses [28].…”
Section: Introductionmentioning
confidence: 99%
“…Research on international migration in Pakistan has primarily addressed a number of concerns which can be summarized as (i) to establish the magnitude and demographic profiles of the out-migrants (ii) the returnmigrant (iii) implications of manpower experts at the macro-level and its broad aggregates (employment of labor force, GNP growth, savings, private investment) and consumption, and (iv) balance of payments [20]. Specifically, the utilization of remittances by migrants' households and by migrant on his return has been the subject of much empirical research mainly to search for incentives and policy prescriptions to channel these resources into productive uses [28].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical analyses, however, have found that workers' remittances may have different impact on economic growth. More specifically, many empirical studies argue that economic growth is positively associated with remittances, especially in developing countries (Kandil and Metwally, 1990;Jongwanich, 2007;Pradhan et al, 2008;Giuliano and Ruiz-Arranz, 2009;Nsiah and Fayissa, 2011;Jouini, 2015;Mayer and Shera, 2017). Some other empirical studies find negative, or insignificant, impact of workers' remittances on economic growth (Chami et al, 2003;Waheed and Aleem, 2008;Jawaid and Raza, 2014;Spatafora, 2005;Barajas et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More details are presented below. Kandil and Metwally (1990) investigates the impact of remittances made by Egyptian migrants to their home country on the Egyptian country using standard Keynesian model over the period from 1970 to 1984. Their results suggest that remittances have a strong positive impact on the Egyptian economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But the value of the multiplier itself depends on the values of propensities to consume. It is important to note here that the more the availability of resources, higher will be the volume of imports that implies an economy to depends on imports (Glytsos, 2005;Kandil, and Metwally, 1999). Remittance plays a vital role toward economic development of any country especially for the developing nations.…”
Section: A Brief Survey Of Literaturementioning
confidence: 99%